Explorando o engajamento, bem-estar, coping e vulnerabilidade do consumidor - Falchetti, Claudia (2020)
Successful pursuit of personal goals contributes to the development and maintenance of individual well-being, and vulnerability situations, which prevent or hinder the individual from achieving consumption goals, can lead to a feeling of reduced well-being for him or her. Understanding the factors that influence consumer well-being and consumer marketplace engagement is essential for academic research, public policy makers and marketers. This doctoral dissertation focuses on the themes of consumer engagement, well-being, coping and vulnerability. This thesis is structured in three distinct studies, presented in the form of scientific articles. The first study, with a theoretical nature, focuses on the well-being and market engagement of the consumer in vulnerability situations, in particular, the disabled consumers. It proposes a conceptual model for these individuals engagement and argues that the most appropriate model for assessing the consumption engagement of these subjects in the marketplace is a model that considers the interaction between consumers and organizations. The second study, involving quantitative research, verifies the relationship between coping, vulnerability and consumer well-being. The results indicated that vulnerability has a negative effect on consumer well-being. The effect of coping on well-being was positive in both studies. In the study 2 there were considered the responses of 199 participants (79 visually impaired and 120 non-disabled). For the problem-focused coping model, the results showed that visually impaired people, compared to non-impaired people, have higher consumption well-being. The third study also included quantitative research and involved 410 participants (210 US residents and 200 from Brazil). It verified, as in the second study, the relationship between coping, vulnerability and consumer well-being, taking into account the respondent's socioeconomic context. The indirect effect of problem-focused coping on well-being mediated by vulnerability was moderated by the respondent's country, but only for Brazilian respondents, the indirect effect of emotion-focused coping on well-being mediated by vulnerability was moderated by context. Taken together, the three studies that make up this doctoral dissertation highlight the importance of organizations' managers and policy makers relying on factors that promote greater consumer well-being in order to develop research projects and programs that improve the quality of life of these people.